Bandwidth sharing scheme in DiffServ-aware MPLS networks - Din N.Md.; Hakimie H.; Fisal N. (2023)
This paper proposes a bandwidth sharing scheme for DiffServ-aware MPLS networks based on the Russian Dolls bandwidth allocation model. Three DiffServ traffic class types were used in the DiffServ-aware MPLS network under study, i.e. real time constant bit rate premium, real time variable bit rate assured and non-real time best effort traffic. We propose a preemption scheme based on rerouting or resizing of the longest existing flow first. A simulation study using ns-2 was performed for the scheme. An analysis was made to show the significance of borrowing and preemption in the environment. The results show significant improvement in terms of blocking probability when both borrowing and preemption are used. 2007 IEEE.